2013
DOI: 10.2298/mpns1312453p
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon rupture - treatment results

Abstract: Early diagnosis and surgical treatment are an absolute imperative in management of this injury. We have not proven that a certain surgical technique has an advantage over the others. A comorbid risk factor is related to a lower Lysholm score. Despite a few cases of complications, we can conclude that the surgical treatment yields satisfactory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Metoda izbora je rano operativno lečenje. Ključne reči: Tetive; Ruptura; Ishod lečenja; Tetiva čašice kolena; Rana dijagnoza; Rekonstruktivne hirurške procedure; Faktori rizika; Opseg pokreta zgloba A patellar tendon rupture occurs most often at its patellar insertion or at the middle of the tendon [2,[5][6][7][8]. In younger patients, this injury occurs because of repeated microtrauma or as a result of taking out medial part of the tendon during anterior cruciate ligament (ACL) reconstruction procedure.…”
Section: Sažetakmentioning
confidence: 99%
“…Metoda izbora je rano operativno lečenje. Ključne reči: Tetive; Ruptura; Ishod lečenja; Tetiva čašice kolena; Rana dijagnoza; Rekonstruktivne hirurške procedure; Faktori rizika; Opseg pokreta zgloba A patellar tendon rupture occurs most often at its patellar insertion or at the middle of the tendon [2,[5][6][7][8]. In younger patients, this injury occurs because of repeated microtrauma or as a result of taking out medial part of the tendon during anterior cruciate ligament (ACL) reconstruction procedure.…”
Section: Sažetakmentioning
confidence: 99%
“…Both uni-and bilateral ruptures were included. As reported by Popov et al (22), this was another factor that could possibly affect the results. Bilateral ruptures were found to have better outcomes than unilateral.…”
Section: Discussionmentioning
confidence: 68%
“…Fourteen studies met inclusion and exclusion criteria and were included in the present review (Table 1). 3,[10][11][12][13][14][15][16][17][18][19][20] The articles included were published between 1977 and 2015. The evaluation of the quality of the included articles revealed that there were two retrospective studies and twelve case reports (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the quality of the included articles revealed that there were two retrospective studies and twelve case reports (Table 1). 15,18 Only patients that presented a BEM rupture were considered and included in this review. 18 The average modified CMS was 37,6 (range from 13 to 53) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation